Perbedaan Kualitas Tidur Lansia yang Tinggal Bersama Keluarga dengan Lansia di PSTW - Muhammad Ischaq Nabil; Wahyu Dewi Sulistyarini (Alma Ata University Press, 2014)
Ageing process has led to physical and functional changing, as well as mental and psychosocial. The sleeping need has also changing as long as ageing. Sleeping quality is inﬂ uenced by several factors including circumstances and living place. The purpose of this research is to compare sleeping quality elderly living with family at Dukuh Kajen Bantul with those living at PSTW Budi Luhur Yogyakarta. This quantitative non experimental study used cross-sectional design. Independent variable in this research was livin place, while dependent variable was sleeping quality on elderly. Data was tested using chi-square and the result was those who lives with family mostly having less sleeping quality at 55 people (49,6%), whereas, quality of sleeping older people lives in PSTW was 41 people (66,1%). Elders who have categorized as less sleeping quality mostly living with family (44,1%) compared with 24,2% who live in PSTW Budi Luhur Yogyakarta. The value Chi-Square was X=6.852 with p value= 0.033. Conclusion, there was signiﬁcant differences on quality of sleeping elderly living with family and living in PSTW Budi Luhur.